2018
DOI: 10.1128/jvi.01992-17
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Specific and Cross-Reactive T Cell Responses to Zika and Dengue Virus NS3 in West Africa

Abstract: responses to African ZIKV and DENV is of relevance to vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 54 publications
5
44
2
Order By: Relevance
“…Unexpectedly, we did not observe T cell responses that were significantly higher in magnitude in individuals with prior DENV exposure. These results are in contrast to our data on African ZIKV infections, which showed that previous flavivirus exposure was associated with enhanced T cell responses (27). One possibility is that the proportion of HIV infection among those with prior DENV exposure was higher compared with DENV-naïve in this study (90.5% versus 50% comparing sDENV and pDENV cases; 83.3% versus 60% comparing ZIKVwpDENV and pZIKV cases).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, we did not observe T cell responses that were significantly higher in magnitude in individuals with prior DENV exposure. These results are in contrast to our data on African ZIKV infections, which showed that previous flavivirus exposure was associated with enhanced T cell responses (27). One possibility is that the proportion of HIV infection among those with prior DENV exposure was higher compared with DENV-naïve in this study (90.5% versus 50% comparing sDENV and pDENV cases; 83.3% versus 60% comparing ZIKVwpDENV and pZIKV cases).…”
Section: Discussioncontrasting
confidence: 99%
“…We recently reported the development of a LFn ELISPOT assay based on NS3 protease and helicase to distinguish DENV and African ZIKV human infections (27). To assess the ability of the assay to distinguish infection by DENV and Asian ZIKV, we performed DENV and ZIKV homologous and heterologous LFn-NS3 protease and helicase stimulation of date-matched late convalescent-phase PBMCs in an IFN-γ and TNF-α ELISPOT among the serological-validated pDENV, pZIKV, sDENV, and ZIKVwpDENV, and undetermined cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, NS3 and NS5 represent the main targets of the CD8 + T cell response to flaviviruses (34, 35). One study reported more cross-reactive T cell responses to full length NS3 helicase, because of higher sequence homology, than that to the protease region alone (36). Also, a homologous analysis based on the NS5 protein would place ZIKV closer to the JEV serocomplex than to DENVs (37).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study it was shown that in two large cohorts from Sri Lanka and Nicaragua (54), the imprint of previous DENV exposure is clearly detectable, and that the resulting T cell response to Asian ZIKV was biased toward the non-structural proteins (Figure 4). Similarly, evidence of pre-existing flavivirus immunity has been shown to result in enhanced T cell responses directed to NS3 of DENV and African ZIKV (69). Whether such responses are protective is unknown, but two studies have demonstrated that short-term T cell cultures of flavivirus specific T cells are capable of killing targets pulsed with peptides that are found in ZIKV, indicating that they likely have anti-viral function ( Figure 5) (20,70).…”
Section: Denv/zikv T Cell Cross-reactivitymentioning
confidence: 98%